2017
DOI: 10.4028/www.scientific.net/aef.24.40
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar and Similar Laser Beam and GTA Welding of Nuclear Fuel Pin Cladding Tube to End Plug Joint

Abstract: The end plug to cladding tube of fast reactor fuel pin is normally welded using Gas Tungsten Arc Welding (GTAW) process. The GTAW process has large heat input and wide heat-affected-zone (HAZ) than high energy density process such as laser welding. In the present study Laser Beam Welding (LBW) is being considered as an alternative welding process to join end plug to clad tube. The characteristics of autogenous processes such as GTAW and pulsed Nd-YAG laser welding on fuel cladding tube to end plug joints have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The main powder was SS316L with addition aluminum powder. It is reported that SS316 austenitic stainless steel is being used for fuel pin cladding tubes in fast nuclear reactor because its good performance at high temperature [15]. Therefore, the aim of the study is to enhanced the performance of SS316 austenitic stainless steel by modified to become an ODS steel with addition of aluminum.…”
Section: Introductionmentioning
confidence: 99%
“…The main powder was SS316L with addition aluminum powder. It is reported that SS316 austenitic stainless steel is being used for fuel pin cladding tubes in fast nuclear reactor because its good performance at high temperature [15]. Therefore, the aim of the study is to enhanced the performance of SS316 austenitic stainless steel by modified to become an ODS steel with addition of aluminum.…”
Section: Introductionmentioning
confidence: 99%